Zdrada Bohdana Slupicza w 1551 r.(okolicznosi zdobycia Braclawia przez Tatarow) - Nykiel, Beata K. (Соціум. Альманах соціальної історії, 2006)
The aim of the text is to shed some light on preconditions and circumstances of the Bratslav defence abilities, as well as on the way the Crimean Tartar siege under the Khan Dewlet Girey in September 1551 developed. In this context the role played by the Bratslav Castle chief defendant Bohdan Siupica acting as his plenipotentiary in the absence of starost Prince Bohusz Korecki is of special interest. A key factor in Bohdan's decisions and activities seams to be the assessment of Bratslav’s defense potential. Bohdan deemed a traitor by his contemporaries as bearing the most blame for the hasty surrender of the castle to the Tartars and the devastation of a large part of the province, in 1551 he disappeared from all the source-mate-rials, and the Siupicas estates were confiscated in forfeiture by escheat. This incident was to affect the history of the entire Siupica family for several decades to come. Thus, the second part of the article traces the way Bohdan’s treason afflicted the Siupicas fate. Special attention is being paid to the efforts of the family representatives aimed to get back the confiscated landed property and to re-establish both its material basis and good standing in the Bratslav area.